2016
DOI: 10.1200/jco.2015.63.7215
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Mortality of Laparoscopic Versus Open D2 Distal Gastrectomy for Advanced Gastric Cancer: A Randomized Controlled Trial

Abstract: Experienced surgeons can safely perform LG with D2 lymphadenectomy for AGC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

46
477
5
20

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 611 publications
(560 citation statements)
references
References 29 publications
46
477
5
20
Order By: Relevance
“…To decrease the mortality and morbidity rates, the inclusion of only appropriate candidates for surgical procedures and the selection of the appropriate LNs for dissection are mandatory. 2 For these reasons, correct intraoperative staging of metastatic LNs is essential for developing an individualized surgery. [3][4][5] Currently, the assessment of regional metastatic LNs is usually conducted via an imagological diagnosis, such as computed tomography (CT), magnetic resonance imaging (MRI) and 18F-fluoro-2-deoxyglucose positron emission tomography (FDG-PET).…”
Section: Introductionmentioning
confidence: 99%
“…To decrease the mortality and morbidity rates, the inclusion of only appropriate candidates for surgical procedures and the selection of the appropriate LNs for dissection are mandatory. 2 For these reasons, correct intraoperative staging of metastatic LNs is essential for developing an individualized surgery. [3][4][5] Currently, the assessment of regional metastatic LNs is usually conducted via an imagological diagnosis, such as computed tomography (CT), magnetic resonance imaging (MRI) and 18F-fluoro-2-deoxyglucose positron emission tomography (FDG-PET).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Katai and colleagues of the Japan Clinical Oncology Group (JCOG0912) confirmed the noninferiority and safety of LADG compared to ODG in terms of short-term adverse and clinical outcomes of 912 early gastric cancer patients (LADG: 457 and ODG: 455 patients) (12 groups were published, in which both studies concluded the non-inferiority of laparoscopic surgeries in early and advanced gastric cancer, respectively (13,14).…”
mentioning
confidence: 99%
“…Equivalent long-term survival outcomes in patients with early gastric cancer were also reported in a randomized control trial (9). Consequently, LG is generally regarded as one of the standard treatments for early gastric cancer, and it is expected that the indications for LG will expand further to advanced gastric cancer (10).…”
Section: Introductionmentioning
confidence: 87%